Association of abnormal vaginal microflora and HPV infection in cervical precancerous lesions: a retrospective study - Huan Yu; Li Ma; Meilu Bian; Qian Li; Haiyan Liang (Journal of Infection in Developing Countries)
Introduction: The aim of this study was to analyze the correlation between abnormal vaginal microflora and different types of human papillomavirus (HPV) infection and cervical precancerous lesions during the perimenopausal period.